2020
DOI: 10.4081/jphia.2019.1044
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HIV testing and counseling among tertiary institution students in the Hohoe Municipality, Ghana

Abstract: HIV Testing and Counselling (HTC) is a critical strategy to reduce the rate of new HIV infections and the key entry point to HIV treatment, care and support services. This study aimed to determine the uptake of HTC among students of tertiary institutions in the Hohoe Municipality of Ghana. This was a quantitative cross-sectional study. A structured questionnaire was used to collect data among a proportionate stratified sample of students from tertiary institutions. Chi-square and Logistic regression analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…Furthermore, studies aimed at increasing awareness to get tested among participants reported a high willingness of the participants to get tested. However, the high willingness to get tested for HIV does not automatically translate into actual testing (Agamlor et al, 2019;Zewudie et al, 2020).…”
Section: Congomentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies aimed at increasing awareness to get tested among participants reported a high willingness of the participants to get tested. However, the high willingness to get tested for HIV does not automatically translate into actual testing (Agamlor et al, 2019;Zewudie et al, 2020).…”
Section: Congomentioning
confidence: 99%
“…A total of 79.3 million people were infected with HIV since the epidemic started and 36.3 million people died from AIDS-related illnesses since the start of the epidemic. Sub-Saharan Africa which consists of just 10% of the world's population, remains the most seriously affected region with a total of 63% of all new infections recorded in 2020 alone (Agamlor et al, 2019) According to the Ghana AIDS Commission, Ghana recorded an HIV prevalence of 1.69% in 2020 with a regional HIV prevalence of 2.66% (highest) in the Ahafo region and a prevalence of 0.39% (lowest) in the North-East region. The Lower Manya Krobo recorded an HIV prevalence of 5.56% (highest) at the district level and 0.07% (lowest) in the Karaga and Tolon districts (GAIDSC, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative effect of HIV is substantial, ranging from stigmatization, acute and chronic ill-health and HIV/AIDS-related deaths as well as the socio-economic burden on the household, community and the country (4,5). Although the annual number of AIDS-related deaths worldwide dropped by 35% between 2005 and 2013, deaths among adolescents (ages 10 to 19) increased by 50% during the same period (7,9). Sub-Saharan Africa forms only 12% of the global population and yet accounts for over half of the burden of HIV infection (7).…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative effect of HIV is substantial, ranging from stigmatization, acute and chronic ill-health and HIV/AIDS-related deaths as well as the socio-economic burden on the household, community and the country (4,5). Although the annual number of AIDS-related deaths worldwide dropped by 35% between 2005 and 2013, deaths among adolescents (ages 10 to 19) increased by 50% during the same period (7,9). Sub-Saharan Africa forms only 12% of the global population and yet accounts for over half of the burden of HIV infection (7).…”
Section: Introductionmentioning
confidence: 99%